Trauma bonding and interpersonal crimes - Reid, Joan A. (Wiley series in psycho-criminology of crime, mental health, and the law, 2024)
"The phenomenon of victims developing emotional attachments to their abusers or captors has been observed within situations involving intimate partner violence, child abuse, hostage situations, human trafficking, and cults. This psychological phenomenon, labeled trauma bonding, has been explained as a product of interpersonal trauma. Despite repeated observations of trauma bonding in victims of interpersonal crimes, little is known about its formation or persistence, and even less is known about positive resolution in survivors. The scope of the proposal book includes a review of the existing theoretical conceptualizations and research findings on trauma bonding in relation to various forms of interpersonal crimes including human trafficking, intimate partner violence, child sexual abuse, cults, kidnapping, gangs, and terrorism. The proposed book would also highlight the complexities of intervention and treatment for survivors and clinicians. Each chapter will feature voices of survivors and insights from practitioners on the frontlines to provide a blending of personal reality with the well-researched facts. Critical concerns regarding methodological weaknesses of previous research focused on trauma bonding will be addressed and several potential avenues for integrated theory and research recommended. Lastly, implications for policy related to trauma bonding within the field of interpersonal violence will be explored"--